Development of aqua-loader for fish farming - Tengku Azmi, Tengku Sharifah Marliza; Kupo, Anelka Dau; Surik, Sheralyn Rimba; Rameli, Luqman; Arang, Nelly Uding; Habari, Mohammad Adib Azri; Zainol @ Abdullah, Wan Nor Zanariah (Malaysian Society of Agricultural Engineers, 2019)
Aqua-loader is a multifunction machine that use for harvesting, grading, weighing, and packing the fish. This prototype has been developed in order to conduct a better management in aqua farming that consume cost and time. The objectives of this project are to reduce the time taken in the management of fish farming, to save cost in handling of the fish farming and to suggest a better management to the whole fish farming that can reduce a lot of management errors. Aqua-loader offer valuable benefits to the farmers, which is reducing the cost of labour, to enhance the quality of the product and increase productivity. Aqua-loader also offer a proper and good management for aquaculture and fish industry.